Motivation at Work: Assessing Motivation Factors in Chinese Family Business - Bai, Chang long (2009)
Family business is a kind of emerging business style in China. Because some of Chinese managers blindly or entirely imitate western motivation models to encourage Chinese employees’ behavior without considering Chinese situation carefully, these motivation models do not work optimally. The aim of this dissertation is to find out which motivator is the most effectiveness for improving employees’ behaviors in Chinese family business. Firstly, this dissertation offered the literature review which aimed to let readers understand more clearly about the background of this topic. Secondly, through sending questionnaire, lots of primary data were collected from a Chinese family business. Then the author used SPSS to analyze the data and found out ‘the feeling of fairness’ was the most effectiveness motivator to Chinese employees. Based on this result, this dissertation also illustrated both theoretical and practical implication in final part. Its purpose was to offer a suggestion for general Chinese family business to satisfy their employees’ feeling of fairness.